Participation in Complex and Social Everyday Activities Six Years after Stroke: Predictors for Return to Pre-Stroke Level. - Avvai Singam; Charlotte Ytterberg; Kerstin Tham; Lena von Koch (PLoS ONE)
Background Long-term disability following stroke can lead to participation restrictions in complex and social everyday activities, yet information is lacking on to what extent stroke survivors return to their pre-stroke levels of participation. Objectives The objectives of this study were to investigate the level of participation in complex and social everyday activities 6 years after stroke, to compare this with pre-stroke participation and to identify predictors of returning to pre-stroke levels of participation. Method All patients admitted to Karolinska University Hospital's stroke units during a 1-year period were eligible to participate and 349 patients were recruited. Assessments were made at base-line, 3 months and 6 years using self-reported outcome measures. Participation was assessed using the Frenchay Activities Index (FAI). The 6-year score for each participant was compared to the pre-stroke score, both for the total score and for each domain (domestic chores, leisure/work and outdoor activities). Predictors of having the same or better level of participation at 6 years were identified using logistic regression. Results At 6 years, 121 participants were followed up, 166 were deceased, 44 declined to take part and 18 could not be traced. At 6 years 84% could be described as active (FAI≥15). The same level of participation or better than pre-stroke was found in 35% of participants, in 65% the level was lower. Similar predictors were identified for achieving the same or better level of participation at 6 years for FAI total and the three domains; ability to walk without aids and a lower age at stroke onset, and perceived mobility, participation and recovery at 3 months. Conclusion Six years after stroke, 35% of participants had the same or better level of participation as pre-stroke. Rehabilitation after stroke to improve walking ability and participation might improve long-term participation in complex and social everyday activities.